Study Habits and Academic Performance among Students of Umar Suleiman College of Education, Gashua, Yobe State, Nigeria - Kyauta, Amadu Muktar A.; Dachia, Alhaji Duna (NIU Journal of Humanities, 2018)
The purpose of this study was to examine the relationship between study habits and academic performance among students of Umar Suleiman College of Education Gashua, Yobe State, Nigeria. The study was guided by one stated objectives; To examine whether there is significant relationship between study habits and academic performance among students. The study used descriptive correlational designs with quantitative approach. The population of the study was NCE three students. Kragcie and morgan table for selection of the sample size was used to select sample size. The drawn sample size was 263. While purposive and simple random sampling techniques were employed to select respondents. Data was collected using close ended adapted - questionnaire with 32 items based on five likert scale which was distributed to the respondents. The data was analyzed in SPSS version 22.0 using frequency tables and percentage to analyses the profile of the respondents and Pearsonâ€™s linear correlation coefficient was used to analyses the data collected from the field according to the study objective. The study found that there is a significant relationship between study habits and academic performance among students of Umar Suleiman college of Education, Gashua, Yobe State, Nigeria. Based on the study findings, the following recommendation was made. The study recommended that school counselors, teachers and authorities should motivate, encourage otherwise enforce reading culture or â€œprep timeâ€ into the curricular and equip the school with reading desk, efficient power supply and facilities that will motivate students to  form good study habits in order to improve and achieve good academic performance. Keywords: Study Habits Academic Performance Students